RHEOLOGY AND FLUID DYNAMIC OF EGG WHITE: EFFECT OF THIXOTROPY ON ENGINEERING DESIGN - Polachini, Tiago Carregari [UNESP]; Basso, Rodrigo Correa; Telis-Romero, Javier [UNESP] (Wiley-Blackwell, 2017)
The wide application of egg products by food industries reinforces the importance of dealing with egg white properties, such as thermophysical ones, for correct processing and equipment design. Therefore, rheological properties, density and pressure drops were studied from 0.5 to 53.4C, as well as their influence on the energy pump required in a hypothetical pipeline configuration. Egg white presented Power-Law behavior, with thixotropy. Consistency coefficient and apparent viscosity were estimated by an Arrhenius-type equation for downward and upward curves. Densities were obtained as a linear function of temperature. Fanning friction factors could be calculated and correlated with generalized Reynolds number. The use of Rabinowitsch-Mooney equation resulted in good similarity with the rheological behavior obtained using the rheometer. Different cases of pipeline simulation showed a deviation of until 2.8% in the required energy pump.